The Right Light: De Novo Design of a Robust Modular Photochemical Reactor for Optimum Batch and Flow Chemistry. Issue 1 (25th September 2019) - Bonfield, Holly E.; Mercer, Kayleigh; Diaz‐Rodriguez, Alba; Cook, Gemma C.; McKay, Blandine S. J.; Slade, Pawel; Taylor, George M.; Ooi, Wei Xiang; Williams, Jason D.; Roberts, Jack P. M.; Murphy, John A.; Schmermund, Luca; et al.
Abstract: Having identified inconsistencies when repeating literature examples of photochemical transformations and difficulties recreating experimental setups, we devised several criteria that an ideal lab‐scale reactor should achieve. Herein, we introduce a versatile photoreactor for high‐throughput screening, preparative‐scale batch reactions and continuous processing, all with a single light source. The reactor utilizes interchangeable arrays of pseudo‐monochromatic high‐power LEDs in a range of synthetically useful wavelengths, combined with excellent temperature control. Moreover, light intensity can be modulated in an accurate and straightforward manner. This system has subsequently been tested on a range of literature methodologies. Abstract : The Right Light : A new commercial photoreactor was examined by performing several photochemical literature reactions. Our workflow is presented in the hope that others adopt the same methodology to begin the process of developing a standardized photochemical platform across academia and industry, that can be utilized by chemists to perform photochemistry in a high‐throughput manner whilst simultaneously developing the in‐depth reaction understanding required.